Phytochemical analysis and anticancer effect of Camellia oleifera bud ethanol extract in non-small cell lung cancer A549 cells - Niu, Jingming; Jia, Xiaoyan; Yang, Nian; Ran, Yuanquan; Wu, Xia; Ding, Furong; Tang, Dongxin; Tian, Minyi (Frontiers in Pharmacology, 2024)
Camellia oleifera is a medicine food homology plant widely cultivated in the Yangtze River Basin and southern China due to its camellia oil. C. oleifera bud and fruit exist simultaneously, and its bud is largely discarded as waste. However, C. oleifera bud has been used in traditional Chinese medicine to treat a variety of ailments. Thus, the purpose of this study was to identify the chemical components of C. oleifera bud ethanol extract (EE) and first evaluate its anticancer effects in non-small cell lung cancer A549 cells. Based on UHPLC-Q-Orbitrap-MS analysis, seventy components were identified. For anticancer activity, C. oleifera bud EE had remarkable cytotoxic effect on non-small cell lung cancer A549 (IC 50 : 57.53 ± 1.54 μg/mL) and NCI-H1299 (IC 50 : 131.67 ± 4.32 μg/mL) cells, while showed lower cytotoxicity on non-cancerous MRC-5 (IC 50 > 320 μg/mL) and L929 (IC 50 : 179.84 ± 1.08 μg/mL) cells. It dramatically inhibited the proliferation of A549 cells by inducing cell cycle arrest at the G1 phase. Additionally, it induced apoptosis in A549 cells through a mitochondria-mediated pathway, which decreased mitochondrial membrane potential, upregulated Bax, activated caspase 9 and caspase 3, and resulted in PARP cleavage.Wound healing and transwell invasion assays demonstrated that C. oleifera bud EE inhibited the migration and invasion of A549 cells in a dose-dependent manner. The above findings indicated that C. oleifera bud EE revealed notable anticancer effects by inhibiting proliferation, inducing apoptosis, and suppressing migration and invasion of A549 cells. Hence, C. oleifera bud ethanol extract could serve as a new source of natural anticancer drugs.